1982
DOI: 10.1115/1.3253217
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface and Surface Cracking Due to Hertzian Contact

Abstract: Numerical results are presented for a cracked elastic half-space surface-loaded by Hertzian contact stresses. A horizontal subsurface crack and a surface breaking vertical crack are contained within the half-space. An attempt to correlate crack geometry to fracture is made and possible mechanisms for crack propagation are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(55 citation statements)
references
References 0 publications
4
51
0
Order By: Relevance
“…Our previous work on crack growth in Stage I (shear cracks) forms the basis for our simulations in this study [8]. We extend the work to determination of crack tip opening ( There have been a number of investigations that focused on determining stress intensity levels for cracks subjected to RCF [13][14][15]. The I K ∆ (stress intensity factor range (SIF)) was shown to approach zero beyond a 'critical' crack length [13] which depends on the loading conditions and orientation of the crack [14].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Our previous work on crack growth in Stage I (shear cracks) forms the basis for our simulations in this study [8]. We extend the work to determination of crack tip opening ( There have been a number of investigations that focused on determining stress intensity levels for cracks subjected to RCF [13][14][15]. The I K ∆ (stress intensity factor range (SIF)) was shown to approach zero beyond a 'critical' crack length [13] which depends on the loading conditions and orientation of the crack [14].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Coy et al [8] applied the Lundberg-Palmgren model [9] to analyze the dynamic capacity and surface fatigue life of spur and helical gears. Keer et al [10,11] analyzed subsurface and surface cracking due to Hertzian contact and suggested a pitting model for rolling contact fatigue using a half-space condition, Hertzian stress theory and the body force method in conjunction with a Paris law (2D fracture mechanics). Murakami et al [12] analyzed surface crack propagation on a lubricated rolling contact using the body force method in conjunction with finite element analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6]). Cracks can nucleate both at the contact surface and subsurface, generally in the presence of defects [7]. Also in the latter case, they can grow under repeated contact loading to produce surface-breaking cracks, which, clear symptom of RCF, have been the focus of much of the existing research.…”
Section: Introductionmentioning
confidence: 99%